El valle de los negros - Salgado, Richard, 1973-; Luna, Miguel (Colectivo Rectángulo, 2016)
"In the Azapa Valley (Chile), a group of descendants of enslaved men and women brought from Africa are organizing the first African census in the history of Chile. Their aim is to get official recognition from the State that has concealed their culture and African identity for more than 200 years."